Aliphatic Polycarbonates Based on Carbon Dioxide, Furfuryl Glycidyl Ether, and Glycidyl Methyl Ether: Reversible Functionalization and Cross‐Linking. Issue 2 (19th November 2014) - Hilf, Jeannette; Scharfenberg, Markus; Poon, Jeffrey; Moers, Christian; Frey, Holger; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> Well‐defined poly((furfuryl glycidyl ether)‐co‐(glycidyl methyl ether) carbonate) (P((FGE‐co‐GME)C)) copolymers with varying furfuryl glycidyl ether (FGE) content in the range of 26% to 100% are prepared directly from CO2 and the respective epoxides in a solvent‐free synthesis. All materials are characterized by size‐exclusion chromatography (SEC), 1H NMR spectroscopy, and differential scanning calorimetry (DSC). The furfuryl‐functional samples exhibit monomodal molecular weight distributions with <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh372v5rn9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Mw¯/M¯n</alternatives> in the range of 1.16 to 1.43 and molecular weights (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh372v5s99" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M¯n</alternatives>) between 2300 and 4300 g mol−1. Thermal properties reflect the amorphous structure of the polymers. Both post‐functionalization and cross‐linking are performed via Diels–Alder chemistry using maleimide derivatives, leading to reversible network formation. This transformation is shown to be thermally reversible at 110 °C. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>